Church and war: A change in hermeneutical stance among Pentecostals - Marius Nel (Verbum et Ecclesia, 2017)
At its inception and for the first 40 years of its existence, Pentecostalism was a pacifist movement preaching non-violence and non-retaliation. At the end of the Second World War, the movement changed its stance, in many instances without officially taking a decision at formal platforms, because of the changes that occurred when its members became socially and economically mobile and the movement strove to be accepted in society. The article argues that the changes were, however, essentially because of a change in its hermeneutical viewpoint that introduced a new climate within the movement, accompanied by various changes in viewpoint and practice. After the 1970s, several theologians within the Pentecostal movement formulated a hermeneutics that concurred to a large degree with the way early Pentecostals viewed and interpreted the Bible. This new hermeneutics allows Pentecostals to rethink their non-pacifist stance and the article argues the case for such a reconsideration. Intradisciplinary and/or interdisciplinary implications: While the classical Pentecostal movement supported pacifism for the first 30 years of its existence, it changed its stance at the end of the Second World War because of new hermeneutical choices. Recent changes in hermeneutical viewpoint within (a part of) the movement require that the ethical issue of pacifism be rethought if it does not want its witness about Jesus Christ as the source of peace to be compromised.